2022
DOI: 10.1186/s12866-022-02548-4
|View full text |Cite
|
Sign up to set email alerts
|

Antimicrobial activity of supernatants produced by bacteria isolated from Brazilian stingless bee’s larval food

Abstract: Background The discovery of new molecules with antimicrobial properties has been a promising approach, mainly when related to substances produced by bacteria. The use of substances produced by bees has evidenced the antimicrobial action in different types of organisms. Thus, the use of bacteria isolated from larval food of stingless bees opens the way for the identification of the new molecules. The effect of supernatants produced by these bacteria was evaluated for their ability to inhibit the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 55 publications
(40 reference statements)
0
5
0
Order By: Relevance
“…Certain microbial species of the honey‐associated microbiome or other derivatives can produce postbiotic compounds able to control the growth of opportunistic pathogens of bees, as well as provide symbiotic benefits (Baharudin et al., 2021; de Paula et al., 2021; Ngalimat et al., 2019; Rosa et al., 2003; Santos et al., 2022). There is evidence of great diversity in the Meliponini ‐associated microbiota, such as viruses, bacteria, yeasts, and filamentous fungi (Echeverrigaray et al., 2021; Leonhardt & Kaltenpoth, 2014; Silva et al., 2017; Villegas‐Plazas et al., 2018).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Certain microbial species of the honey‐associated microbiome or other derivatives can produce postbiotic compounds able to control the growth of opportunistic pathogens of bees, as well as provide symbiotic benefits (Baharudin et al., 2021; de Paula et al., 2021; Ngalimat et al., 2019; Rosa et al., 2003; Santos et al., 2022). There is evidence of great diversity in the Meliponini ‐associated microbiota, such as viruses, bacteria, yeasts, and filamentous fungi (Echeverrigaray et al., 2021; Leonhardt & Kaltenpoth, 2014; Silva et al., 2017; Villegas‐Plazas et al., 2018).…”
Section: Resultsmentioning
confidence: 99%
“…There is evidence of great diversity in the Meliponini ‐associated microbiota, such as viruses, bacteria, yeasts, and filamentous fungi (Echeverrigaray et al., 2021; Leonhardt & Kaltenpoth, 2014; Silva et al., 2017; Villegas‐Plazas et al., 2018). The honey‐associated microbiome has been poorly characterized, even though the isolation of bacteria with potential probiotic effects has been reported, mainly Bacillota (Galperin et al., 2022; Oliphant et al., 2022), formerly known as Firmicutes (Pucciarelli et al., 2014; Santos et al., 2022; Shanks et al., 2017; Syed Yaacob et al., 2018; Tang et al., 2021), and Streptomyces species (Cambronero‐Heinrichs et al., 2019; Ngalimat et al., 2019; Promnuan et al., 2009). However, Kimoto‐Nira and Amano (2008) suggested that the antimicrobial activity of raw honey could adversely affect beneficial bacteria of the host such as lactic acid bacteria (Kimoto‐Nira & Amano, 2008).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Wells containing 200 μL of bacteria and LB were used as positive and negative controls for bacterial growth, respectively. The plate was incubated for 24 h at 37 °C ± 0.5 and bacterial growth was evaluated in a microtiter plate reader at 595 nm at 24 h [ 25 ].…”
Section: Methodsmentioning
confidence: 99%
“…Products from stingless bees constitute a source of biomolecules due to their unique composition, high nutritional value, and potential for biotechnological use [ 23 , 24 ]. The honey, geopropolis, and pollen from these bees have anticancer, antioxidant, anti-inflammatory, antimicrobial, among other actions [ 25 – 28 ]. Stingless bee pollen includes pollen grains collected by bees from diverse botanical sources, serving as a potent reservoir of antioxidants due to the presence of flavonoids and phenolic compounds.…”
Section: Introductionmentioning
confidence: 99%